A critical edition of Caroline Norton's Love in 'the world' - Norton, Caroline Sheridan 1808-1877 (Anthem Press, 2023)
Caroline Norton's forgotten novel, which has remained unpublished until now, tells of the perils of courtship facing a naïve young girl Alixe, who has been launched onto the London social season. Her encounters with both a worthy and an undesirable suitor open an intriguing window onto the fashionable society of the 1820s in which Love in 'the World' takes place. In placing her heroine in these predicaments Norton was able to draw upon her own experiences of the bon ton, as the time in which the novel is set coincides with her first ball in March 1826, when she burst upon the scene with all her beauty and brilliance, later recalling, 'I came out [...] to find all London at my feet.' She believed that London could be as callous as the metropolitan social scene might prove treacherous, and in alerting the reader to the dangers of fashionable society she makes ample use of her own observations as a debutante at her first London season. In a highly readable and coherent narrative with an indeterminate ending, which throws a spotlight onto her life and times, the plot of Love in 'the World' initially follows a pattern broadly representative of her own experience before developing in unexpected and surprising ways